2016
DOI: 10.3390/w8020057
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Adaptive Planning to Reduce Flood Risks among Parishes in South Louisiana

Abstract: Residents of south Louisiana face a range of increasing, climate-related flood exposure risks that could be reduced through local floodplain management and hazard mitigation planning. A major incentive for community planning to reduce exposure to flood risks is offered by the Community Rating System (CRS) of the National Flood Insurance Program (NFIP). The NFIP encourages local collective action by offering reduced flood insurance premiums for individual policy holders of communities where suggested risk-reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, subsidies offered were not sufficient to enable lower income households to undertake mitigation, and higher income amenity migrants, whose properties were often second homes, tended to see insurance as a substitute for risk mitigation. Other studies echo the finding that insurance incentives are only effective in encouraging risk mitigation by the relatively affluent (Li and Landry 2014;Paille et al 2016;Osberghaus 2017).…”
Section: Discussionmentioning
confidence: 90%
“…However, subsidies offered were not sufficient to enable lower income households to undertake mitigation, and higher income amenity migrants, whose properties were often second homes, tended to see insurance as a substitute for risk mitigation. Other studies echo the finding that insurance incentives are only effective in encouraging risk mitigation by the relatively affluent (Li and Landry 2014;Paille et al 2016;Osberghaus 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Identifying the determinants of CRS participation-the focus of the present study-has also received some attention (see Ref. [12,16,17,20,46,49]. The results from the reviewed studies showed that communities participating in the CRS have greater flood risks and higher population sizes [16,20], educational attainment levels [9,17], incomes [18,19], tax revenues [17], proportion of senior citizens [17] as well as lower crime and unemployment rates [17].…”
Section: Research On the Crs Programmentioning
confidence: 90%
“…Their study not only provides important information regarding the current state of knowledge on the CRS, but it also identifies research gaps and offers practical recommendations and policy recommendations to emergency and floodplain managers and policymakers, respectively [37]. This systematic review showed that scholars have examined various aspects of the CRS program, including whether the program is effective at reducing flood losses [7,[9][10][11][12][13]16,[38][39][40][41]), the value and effectiveness of specific CRS activities [9,10,13,[41][42][43][44][45][46], and the predictors of CRS scores, ratings, and points [20,43,[46][47][48][49][50]. Scholars have also examined the relationship between the CRS and disaster recovery [51,52], poverty and income inequality [53], as well as migration and development [54].…”
Section: Research On the Crs Programmentioning
confidence: 99%
“…Studies included under FEMA's CRS program indicate that local capacity, flood risk, socioeconomic characteristics, and political economy factors are significant predictors of initial and continuing participation in the CRS program (Asche 2013;Li 2011, 2018;Li 2012;Paille et al 2016;Sadiq and Noonan 2015a, b). This body of research also demonstrates that participation in FEMA's CRS program is indeed an effective strategy for reducing communities' flood losses Brody 2013, 2017).…”
Section: Major Findings From the Community Flood Risk Management Literaturementioning
confidence: 99%